Penerapan Pembelajaran Index Card Match terhadap Kemampuan Pemecahan Masalah Matematika Sekolah Dasar - Hanum Aulia Azzahra; Ni Luh Sakinah Nuraini; Erif Ahdhianto (Universitas Negeri Malang, 2023)
This study was conducted to determine whether there are differences in learning outcomes when applying index card match learning with conventional learning to the mathematical problem solving ability of grade V elementary school students. The research method used is an experiment nonequivalent control group design. The sample of the study was 56 students from grade V of SDN Madyopuro 1. The description test was used for the data collection instrument in this study. The results showed that there were significant differences in learning outcomes when applying index card match learning and conventional learning to students' mathematical problem solving abilities.